(untitled) (Universitas Medica, 2021)
Introduction: The frozen section procedure is an intraoperative diagnostic method widely used and useful for surgical decision making; which minimizes costs and optimizes staging. Objectives: This research assesses the diagnostic accuracy of frozen section in an intermediate care center, analyzes the factors that may be involved in misdiagnosis and compares the results of the original study with other studies. Materials and methods: This is a cross-sectional study in which the diagnostic accuracy was evaluated and a univariate analysis was performed in a sample of 417 cases that underwent a frozen section. The characteristics of the samples were registered along with the concordance or discordance between the frozen section and the final diagnosis. In addition, a systematic review was made using the Pubmed database in order to compare results with previous studies. Results: The sample included predominantly females with a mean age of 50 years. The sensitivity and specificity of malignancies was 89% and 100% respectively and the sensitivity for borderline tumors was lower (73%). Specimens equal or larger than 10cm and patients with age ≥ 50 years showed association to misdiagnosis when using frozen sections. For example, the analysis of 300 ovary specimens showed association to misdiagnosis in borderline, epithelial and stromal tumors. Conclusions: The frozen sections continue to be the best tool for quick intraoperative diagnostic, and even with some inaccuracies in the diagnosis, this don’t harm the clinical and surgical practice.